2017
DOI: 10.1016/j.nucengdes.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The development of a physical model of an Advanced Gas Cooled Reactor core: Outline of the feasibility study

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractThe graphite components in the Advanced Gas Cooled Reactor (AGR) cores are subject to degradation processes that are predicted to lead to greater numbers of weakened and cracked components. These ageing issues need addressing to maintain their safety and reliable operation, hence the requirement for the computer models of the cores used for the seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Instead of graphite, which is brittle, difficult to manufacture, dirty to handle, and subject to dust production through wear during shaking, an engineering plastic called Acetal was selected for the physical model components as it offers increased resilience, and its properties are well matched to that of graphite. A detailed presentation of the design process of the experiment is available in Dihoru et al The rig is an octagonal array of bricks and keys spanning eight layers as shown in plan and side views in Figure . Three types of bricks exist in the array: Lattice bricks (LBs), the larger array parts, which are multifaceted with a cylindrical bore (Figure C and Figure A).…”
Section: Agr Core Physical Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of graphite, which is brittle, difficult to manufacture, dirty to handle, and subject to dust production through wear during shaking, an engineering plastic called Acetal was selected for the physical model components as it offers increased resilience, and its properties are well matched to that of graphite. A detailed presentation of the design process of the experiment is available in Dihoru et al The rig is an octagonal array of bricks and keys spanning eight layers as shown in plan and side views in Figure . Three types of bricks exist in the array: Lattice bricks (LBs), the larger array parts, which are multifaceted with a cylindrical bore (Figure C and Figure A).…”
Section: Agr Core Physical Model Descriptionmentioning
confidence: 99%
“…When testing, the restraint frame is bolted directly to the underlying platform of the University of Bristol shaking table. More information on the restraint system is available in Dihoru et al…”
Section: Agr Core Physical Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several enhanced analytical methods and physical models for static and dynamic behaviour have been reported in the last decade 2,3 . Between 2008 and 2012, a quarter‐scale near‐full single layer 20‐rings array model (“the single‐layer array (SLA)”) was developed at UOB 4 to explore the basic mechanics of the core system as a precursor for a more sophisticated modelling tool: the quarter‐scale 8‐layer‐20‐bricks‐across AGR core model (“the multilayer array (MLA)”) 5 …”
Section: Introductionmentioning
confidence: 99%
“…The model components are made from a rigid engineering plastic (acetal). Details of model design, build and testing have been published (Dihoru et al 2015, Dihoru et al 2016. The rigs were tested extensively on the earthquake simulator, while computer model simulations were run in parallel.…”
Section: Introductionmentioning
confidence: 99%